Enforcement Actions and Auditor Changes. Issue 3 (27th May 2018) - Brocard, Marcus; Franke, Benedikt; Voeller, Dennis
Abstract: In this paper, we examine whether the uncovering of erroneous financial statements by German enforcement agencies is related to subsequent auditor changes. We argue that enforcement actions are likely to reveal information about the client or its auditor, which might affect auditor choice by initiating an update of mutual expectations. Our empirical findings indicate that firms with erroneous financial statements indeed have an increased probability of subsequent auditor changes. Firms also tend to change from a non-Big4 auditor to a Big4 auditor in this situation, suggesting that clients increasingly seek the reputation and services of Big4 auditors. Big4 auditors in turn do not appear to refrain from taking over error-firms as new clients in the German setting, which is characterized by limited auditor liability. Additionally, auditor changes are more likely to occur before the public announcement of an error, indicating that firms take action as soon as the uncovering of an accounting error becomes sufficiently certain.